Faktor – Faktor yang berhubungan dengan Rendahnya Penggunaan Metode Kontrasepsi Jangka Panjang pada Pasangan Usia Subur - Rosa Riya; Rahayu Rahayu (Universitas Baiturrahim, 2023)
The health profile data shows the results of the achievement of active family planning participants per contraceptive device as follows; IUD 7.40%, MOW2, 70%, MOP 0.50%, implants 7.40%, condoms 1.20%, injections 63.70%, and pills 17.00%. The data shows that short-term contraception is the people's main choice. This study aims to determine the factors associated with the low use of MKJP. This study used a cross sectional design. The population in this study were PUS Kampung KB Pulau Village, Muara Tembesi District, Batang Hari Regency, namely 285 with a total sampling of 285 people by distributing questionnaires and analyzed univariately and bivariately. The results showed that there was a relationship between knowledge (p=0.000), attitude (p=0.000), spousal support (p=0.006) and socio-cultural (p=0.005) with low use of MKJP in EFA in Kampung KB Desa Pulau Kec. Batang Hari estuary.